Genome sequencing and metabolic network reconstruction of a novel sulfur-oxidizing bacterium Acidithiobacillus Ameehan - Wu, Peng; Yuan, Qianqian; Cheng, Tingting; Han, Yifan; Zhao, Wei; Liao, Xiaoping; Wang, Lu; Cai, Jingyi; He, Qianqian; Guo, Ying; Zhang, Xiaoxia; Lu, Fuping; et al. (Frontiers in Microbiology, 2023)
Sulfur-oxidizing bacteria play a crucial role in various processes, including mine bioleaching, biodesulfurization, and treatment of sulfur-containing wastewater.Nevertheless, the pathway involved in sulfur oxidation is highly intricate, making its complete comprehension a formidable and protracted undertaking. The mechanisms of sulfur oxidation within the Acidithiobacillus genus, along with the process of energy production, remain areas that necessitate further research and elucidation. In this study, a novel strain of sulfur-oxidizing bacterium, Acidithiobacillus Ameehan, was isolated and its complete genome sequence was presented. Several physiological characteristics of the strain were verified in the study. These characteristics included morphological size and an optimal growth temperature range of 37-45℃, as well as an optimal growth pH range of pH 2.0-8.0. The microbe was found to be capable of growth when sulfur and K2O6S4 were supplied as the energy source and electron donor for CO2 fixation. Conversely, it could not utilize Na2S2O3, FeS2, FeSO4•7H2O as the energy source or electron donor for CO2 fixation, nor could it grow using glucose or yeast extract as a carbon source. Genome annotation revealed that the bacterium possessed a series of sulfur oxidizing genes that enabled it to oxidize elemental sulfur or various reduced inorganic sulfur compounds (RISCs). In addition, the bacterium also possessed carbon fixing genes involved in the incomplete Calvin-Benson-Bassham (CBB) cycle. However, the bacterium lacked the ability to oxidize iron and fix nitrogen. In order to gain a comprehensive understanding of the metabolic capacity of the strain, the first genome-scale metabolic network model (AMEE_WP1377) was reconstructed for Acidithiobacillus Ameehan. By implementing a constraint-based flux analysis to predict cellular growth in the presence of 71 carbon sources, 88.7% agreement with experimental Biolog data was observed. Five sulfur oxidation pathways were discovered through model simulations. The optimal sulfur oxidation pathway had the highest ATP production rate of 14.81 mmol/gDW/h, NADH/NADPH production rate of 5.76 mmol/gDW/h, consumed 1.575 mmol/gDW/h of CO2 and 1.5 mmol/gDW/h of sulfur. Our findings provide new insights into the most efficient pathways of cellular metabolism in Acidithiobacillus Ameehan, which could have potential biotechnological applications.